A passion for democracy : American essays - Barber, Benjamin R., 1939-2017 (Princeton University Press, 2000)
"Benjamin Barber is one of America's preeminent political theorists. He has been a significant voice in the continuing debate about the nature and role of democracy in the contemporary world. A Passion for Democracy collects twenty of his most important writings on American democracy. In these pieces, Barber argues for participatory democracy without dependence on abstract metaphysical foundations, and he stresses the relationship between democracy and civil society, civic education, and culture."--Jacket.